Fine structure of the male reproductive ducts, vagina and seminal receptacle of Cyathocephalus truncatus (Cestoda: Spathebothriidea) - Poddubnaya, Larisa G; Mackiewicz, John S; Brunanská, Magdaléna; Dezfuli, Bahram S (Folia parasitologica, 2005)
Fine structure of the vas efferens, vas deferens, ejaculatory duct with accessory glands and vagina with seminal receptacle is described in the spathebothriidean tapeworm, Cyathocephalus truncatus (Pallas, 1781) Kessler, 1868. The numerous well-developed prostate glands are characterised by having secretory granules with an electron-dense core surrounded by a matrix of lower electron density. Coalescence of the outer part of the granules with each other takes place in the terminal end of the secretory ducts. The position of prostate glands around the proximal part of the cirrus pouch and terminating in the ejaculatory duct is a characteristic feature of the Spathebothriidea. Up to 20 closely arranged muscle layers make up the muscular cirrus pouch wall with 4 well-developed muscular layers in the ejaculatory duct and cirrus. Both the cirrus and the vagina are covered with the same uniform cone-shaped microtriches. The vagina has an extensive seminal receptacle. All of these structures are well-adapted to insure successful sperm transfer involving ejaculation and storage, probably for both self- and cross-insemination. Cyathocephalus truncatus has a cirrus similar to that of the monozoic, progenetic caryophyllidean, Archigetes sieboldi and well-developed prostate glands like those of the polyzoic pseudophyllidean, Diphyllobothrium latum. The ultrastructural aspects of the male and female reproductive system of C. truncatus are compared with those of other tapeworms.
Keywords: Cestoda; Rusko; transmisní elektronová mikroskopie; Russia; Male; Genitalia; Animals; Salmonidae; Italy; pohlavní orgány; mužské pohlaví; ženské pohlaví; Female; Microscopy, Electron, Transmission; Itálie; zvířata